ERS-Tool: Hybrid model for software requirements elicitation in Spanish language - Apaza R.D.G. (2018)
The nature of the software requirements is subjective and varied. For this reason the level of complexity increases according to the volume, especially when the requirements are made in a natural language. Therefore obtain quality software requirements that are understandable and unambiguous in the Spanish language becomes a necessity.